Inflammatory phenotypes predict changes in arterial stiffness following ART initiation - Kelly, C; Tinago, W; Alber, D; Hunter, P; Luckhurst, N; Connolly, J; Arrigoni, F; Abner, AG; Kamngona, R; Sheha, I; Chammudzi, M; Jambo, K; et al. (Oxford University Press, 2020)
Background Inflammation drives vascular dysfunction in HIV, but in low-income settings causes of inflammation are multiple, and include infectious and environmental factors. We hypothesised that patients with advanced immunosuppression could be stratified into inflammatory phenotypes that predicted changes in vascular dysfunction on ART.